2018
DOI: 10.1021/acsanm.8b00645
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Treatment of Metal Oxide Nanoparticles: Development of Core–Shell Structures for a Better and Similar Dispersibility

Abstract: Low-pressure plasma polymerization of cyclopropylamine was employed for the surface functionalization of commercial ZnO, Al 2 O 3 , and ZrO 2 nanoparticles in a homemade hollow cathode plasma reactor. The analysis of the modified nanoparticles by X-ray photoelectron spectroscopy (XPS) revealed the incorporation of reactive functional groups such as primary and secondary amines, which was confirmed by Fourier transform infrared spectroscopy (FTIR). The raw and the plasma functionalized nanoparticles were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The plasma reactor has been extensively described in previous studies, 22,23,55 which are summarized in the recent review of Vandenabeele and Lucas. 57 In summary, the reactor consists of a cylindrical drum maintained on a grounded iron support, which contains a block of magnets.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma reactor has been extensively described in previous studies, 22,23,55 which are summarized in the recent review of Vandenabeele and Lucas. 57 In summary, the reactor consists of a cylindrical drum maintained on a grounded iron support, which contains a block of magnets.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The reactor is a home-made cylindrical magnetron reactor that was designed for the surface modification of powders and has already been used for the functionalization of carbon nanotubes 22 and metal oxide nanoparticles. 23 The precursor chosen is cyclopropylamine (CPA, C3H7N), which is a non-toxic isomer of the highly studied allylamine molecule, and which has recently shown a great potential to deposit stable PPFs with high content of primary amine groups. [24][25][26][27][28][29][30][31][32][33] Plasma modelling is extensively used to help understanding of plasma processes, to predict final coatings properties, to optimize plasma chambers and to ease the scaling-up of a process.…”
Section: Introductionmentioning
confidence: 99%
“…The total atomic concentration of C, O, and N atoms in the FA molecule grafted to the BNNPs (hereafter denoted as C FA ) was estimated assuming that there was no hydrogen in the BNNPs (according to XPS data) and the FA has the chemical formula C 19 H 19 N 7 O 6 . Taking into account the number of N atoms in one FA molecule (C 19 H 19 N 7 O 6 ), the C FA = 3.8 at.% value was obtained by dividing the ∆N by 7 and multiplying this value by the total number of C (19), O (6), and N (7) atoms in one FA molecule. Note that additional C 1s and O 1s signals from both BNNP surface contaminations and BNNP-supported carbon tape can affect the results of quantitative XPS analysis.…”
Section: Xps Spectroscopymentioning
confidence: 99%
“…The monomer selection was carried out based on available literature data, which have shown high stability and reactivity of the CPA films. Recently, LP plasma polymerization of CPA to functionalize ZnO, Al 2 O 3 , and ZrO 2 NPs has been successfully tested [19]. TEM images clearly demonstrated that a thin (5 nm) plasma polymer film was formed on the surface of individual NPs, while the remaining NPs remained uncoated.…”
Section: Introductionmentioning
confidence: 99%
“…), many of which may induce a wide range of changes upon collision with a target surface. [29,30] Plasma modification of surfaces is a frequently neglected approach to the processing of metal oxides, [31,32] despite its demonstrable advantages in the modification of the materials, in particularly, its high degree of control in comparison with other techniques. [33][34][35] For example, Yu et al used a plasma source for the rapid deposition of SnO 2 films in the form of sol-gel.…”
Section: Introductionmentioning
confidence: 99%